Cessation of facial growth in subjects with short, average, and long facial types – Implications for the timing of implant placement. Issue 10 (December 2015) - Aarts, B.E.; Convens, J.; Bronkhorst, E.M.; Kuijpers-Jagtman, A.M.; Fudalej, P.S.
Abstract: Placement of a single-tooth implant should be performed when a patient's facial growth has ceased. In this retrospective observational study, we evaluated if there was a difference in the timing of cessation of craniofacial growth in short, average, and long facial types. Based on the value of the angle between cranial base and mandibular plane (SN/MP angle), three groups comprising 48 subjects with short facial type (SF; SN/MP ≤28°), 77 with average facial type (AF; SN/MP ≥31.5° and ≤34.5°), and 44 with long facial type (LF; SN/MP ≥38°) were selected. Facial growth was assessed on lateral cephalograms taken at 15.4 years of age, and 2, 5, and 10 years later. Variables were considered to be stable when the difference between two successive measurements was less than 1 mm or 1°. We found no difference between facial types in the timing of cessation of facial growth. Depending on the variable, the mean age when variables became stable ranged from 18.0 years (Is-Pal in LF group) to 22.0 years (SN/MP in LF group). However, facial growth continued at the last follow-up in approximately 20% subjects. This study demonstrates that facial type is not associated with the timing of cessation of facial growth.